Isosorbide-Based Thermoplastic Polyurethane with Different Polyols and Soft/Hard Ratios - Jin-Gyu Min; Won-Bin Lim; Ju-Hong Lee; Chung Ryeol Kwon; Gwang-Seok Song; Ji-Hong Bae; PilHo Huh (Advances in Polymer Technology, 2023)
A series of isosorbide-based thermoplastic polyurethanes (ISB-TPUs) with different soft/hard ratios have been successfully step polymerized using individual two types of polycaprolactone diol (PCL) or poly (tetramethylene glycol) (PTMG) for soft segment and bio-based isosorbide (ISB) or methylene diphenyl diisocyanate (MDI) for hard segment, based on the similar molecular weight. The effect of the molecular structure on the mechanical and thermal properties has been evaluated in terms of the types of soft/hard and polyol, ranging from 6/4 to 9/1 ratio values. With the increasing of PCL content, the thermal properties of the ISB-TPU have enhanced gradually. When the range from PCL was 6/4, the tensile strength has achieved the maximum value in comparison with that of the PTMG block. Elongation at break has increased with the increase of hard segment concentration, due to the superior interaction between ester groups and urethane groups. The obtained ISB-TPUs can be a promising resin for soft, flexible, and biocompatible application fields.